Highly pathogenic avian influenza A(H5N1) in animals: A systematic review and meta-analysis - Bonilla-Aldana, D. Katterine (2024)
Introduction: Avian influenza A H5N1 is a significant global public health threat. Although relevant, systematic reviews about its prevalence in animals are lacking. Methods: We performed a systematic literature review in bibliographic databases to assess the prevalence of H5N1 in animals. A meta-analysis with a random-effects model was performed to calculate the pooled prevalence and 95 % confidence intervals (95%CI). In addition, measures of heterogeneity (Cochran's Q statistic and I2 test) were reported. Results: The literature search yielded 1359 articles, of which 33 studies were fully valid for analysis, including 96,909 animals. The pooled prevalence for H5N1 in birds (n = 90,045, 24 studies) was 5.0 % (95%CI: 4.0–6.0 %; I2 = 99.21); in pigs (n = 3,178, 4 studies) was 1.0 % (95%CI: 0.0–1.0 %); in cats (n = 2,911, 4 studies) was 0.0 % (95%CI: 0.0–1.0 %); and in dogs (n = 479, 3 studies) was 0.0 % (95%CI: 0.0–2.0 %). Conclusions: While the occurrence of H5N1 in animals might be comparatively limited compared to other influenza viruses, its impact on public health can be substantial when it transmits to humans. This virus can potentially induce severe illness and has been linked to previous outbreaks. Therefore, it is essential to closely monitor and comprehend the factors influencing the prevalence of H5N1 in both avian and human populations to develop effective disease control and prevention strategies